Comparing integrative ventilatory and renal acid–base acclimatization in lowlanders and Tibetan highlanders during ascent to 4,300 m - Nicole A. Johnson; Jessica A. Dickenson; Benjamin W.L. MacKenzie; Rodion Isakovich; Anne Kalker; Janne Bouten; Nicholas D.J. Strzalkowski; Taylor S. Harman; Pontus Holmström; Ajaya J. Kunwar; Nilam Thakur; Sunil Dhungel; et al. (Proceedings of the National Academy of Sciences, 2025)
With over 14 million people living above 3,500 m, the study of acclimatization and adaptation to high altitude in human populations is of increasing importance, where exposure to high altitude (HA) imposes a blood oxygenation and acid–base challenge. A sustained and augmented hypoxic ventilatory response protects oxygenation through ventilatory acclimatization, but elicits hypocapnia and respiratory alkalosis. A subsequent renally mediated compensatory metabolic acidosis corrects pH toward baseline values, with a high degree of interindividual variability. Differential renal compensation between acclimatizing lowlanders (LL) and Tibetan highlanders (TH; Sherpa) with ascent was previously unknown. We assessed ventilatory and renal acclimatization between unacclimatized LL and TH during incremental ascent from 1,400 m to 4,300 m in age- and sex-matched groups of 15-LL (8F) and 14-TH (7F) of confirmed Tibetan ancestry. We compared respiratory and renally mediated blood acid–base acclimatization (PCO 2 , [HCO 3 − ], pH) in both groups before (1,400 m) and following day 8 to 9 of incremental ascent to 4,300 m. We found that following ascent to 4,300 m, LL had significantly lower PCO 2 ( P <0.0001) and [HCO 3 − ] ( P <0.0001), and higher pH ( P = 0.0037) than 1,400 m, suggesting respiratory alkalosis and only partial renal compensation. Conversely, TH had significantly lower PCO 2 ( P < 0.0001) and [HCO 3 − ] ( P < 0.0001), but unchanged pH ( P = 0.1), suggesting full renal compensation, with significantly lower PCO 2 ( P = 0.01), [HCO 3 − ] ( P < 0.0001) and pH ( P = 0.005) than LL at 4,300 m. This demonstration of differential integrative respiratory–renal responses between acclimatizing LL and TH may indicate selective pressure on TH, and highlights the important role of the kidneys in acclimatization.